Synthesis of Novel Tetra-Substituted Pyrazole Derivatives from 2,3-Furandione - Genç, Hasan; Taşdemir, Volkan; Tozlu, İsrafil and Ögün, Erdal (Letters in Organic Chemistry, 2019)
Synthesis of pyrazole-3-carboxylic acid was progressed via two different protocols, one of which is solid state. Pyrazole-3-carboxylic acid was converted into different derivatives such as ester, urea, amide and nitrile. The amide compound was converted to nitrile using SOCl2 and DMF. Solid state heating of carboxylic acid gave decarboxylated product. Cyclization of tetra-substituted pyrazole with hydrazines resulted in pyrazolopyridazinones. The antimicrobial activities of the synthesized pyrazole derivatives against Bacillus cereus, Escherichia coli, Micrococcus luteus, Staphylococcus aureus, and Saccharomyces cerevisiae were evaluated. One of the pyrazole derivatives which possess nitro group showed antimicrobial activity in only B. cereus, a Gram-positive bacteria, with an MIC of 128 μg/mL.
Keywords: pyrazole